PENGARUH KESELAMATAN DAN KESEHATAN KERJA (K3) TERHADAP PRODUKTIVITAS KERJA KARYAWAN DI PT PLN (PERSERO) - Annisa Wirdayani (CV. ADIBA AISHA AMIRA, 2023)
Undoubtedly, human resources play an important role in the success of any company or entity. HR is a critical asset that requires special attention and care. This research focuses on workers at PT PLN (Persero) due to their non-compliance with the requirements for Personal Protective Equipment (PPE), which causes significant safety hazards. There is a real need to improve managerial oversight given the lack of employee involvement in Occupational Safety and Health (OHS) training and the workplace environment. Researchers at PT PLN (Persero) conducted an analysis to determine the causal relationship between Occupational Safety and Health (K3) and worker productivity. The aim of various initiatives that fall under the scope of